Research methods in consumer law : a handbook - Micklitz, Hans-Wolfgang, 1949-; Sibony, Anne-Lise; Esposito, Fabrizio; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2018)
European consumer law seeks to ensure that consumers receive sufficient information about goods and services, are not subject to unfair contract clauses or unfair commercial practices and have the means to redress grievances. This Handbook specifically considers the impacts of different disciplines and methods as it presents the state of the art in consumer law research and in particular offers intriguing new insights from behavioural science. Research Methods in Consumer Law shows how different lenses help to highlight under-researched areas of consumer law and engage with current debates in order to suggest pertinent legal reforms. Rules meant to protect consumers are often premised on the fact that small print is read, understood and acted upon. Acknowledging that this is rarely the case, the expert contributors offer new perspectives, informed by the study of how real people behave and paying careful attention to methodology. Offering the tools to engage in promising and socially useful legal research, this Handbook will appeal to students and scholars across the fields of law and behavioural science, as it offers a fresh look at the relation between EU consumer law and other disciplines oriented to solving practical problems.
1. The bright and adventurous future of consumer law research / Hans-W. Micklitz, Anne-Lise Sibony, Fabrizio Esposito -- Part I -- Foundations of behavioural consumer legal research -- 2. Conceptual foundations for a European consumer law and behavioural sciences scholarship / Fabrizio Esposito -- 3. Nudging and autonomy. A philosophical and legal appraisal / Philipp Hacker -- 4. Rational choice and behavioural approaches to consumer issues / Fernando Gómez Pomar1 and Mireia Artigot Golobardes -- Part II -- Advances in behavioural consumer legal research -- 5. The role(s) of empirical research in consumer law and consumer law scholarship / Anne-Lise Sibony -- 6. US behavioural consumer research / Franziska Weber -- 7. Who calls the tune?: stock taking of behavioural consumer protection in Europe / Joasia Luzak -- 8. Regulatory validity / Kai Purnhagen -- 9. Behavioural innovations in marketing law professor / Jan Trzaskowski -- 10. A behavioural perspective on consumer finance / Genevieve Helleringer -- Part III Insights from broader perspectives -- 11. How behavioural research has informed consumer law: the many faces of behavioural research / Michiru Nagatsu and Magdalena Małecka -- 12. What is the 'social' in behavioural economics?: the methodological underpinnings of governance by nudges / Sabine Frerichs -- 13. Behavioural analysis and socio-legal research - is everything architecture? / Florian Möslein -- 14. Behavioural analysis and comparative law - improving the empirical foundation for comparative legal research / Giesela Rühl -- 15. The politics of behavioural economics of law / Hans-W. Micklitz -- Index.
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: ochrana spotřebitele; consumer protection; e-knihy online; e-books online